The Decorative Orientations in the Mediterranean Architecture and its Influence on the Development of Cultural Sustainability - Hukmat, Sara; Uzunahmet, Havva Arslangazi (European Journal of Sustainable Development, 2020)
This paper attempts to describe the different orientations in architectural decoration that arose as a result of human existence and its relation to his environment. Throughout history, decoration has been a bridge connecting the building to the environment, connecting people with history and culture. And it has been an instrument of the local identity of the building and the whole environment within the framework of the idea of sustainability, which consists of three foundations (economic, environmental and cultural). Within this texture in this study, decorative details and patterns are evaluated, in order to understand the effects of factors on cultures. From one culture to another, it is discussed in connection with the comparison of the Moorish and Greek decoration. As a result, this study has determined decorative orientations in the Mediterranean architecture and its influence on sustainable development. Keywords: Decoration, Cultural Sustainability, Style, Identity, Greek, Moorish